Dating Methods of Pleistocene Deposits and Their Problems: The Promise of Atom Counting - Litherland, Albert Edward (Geoscience Canada, 1979)
Recent developments in mass spectrometry, using some of the apparatus and techniques of nuclear physics, have made possible the detection of the cosmic ray created 14C, 10Be and 36C1 nuclei at natural concentrations by atom counting. The small sample size, a few milligrams, promises to revolutionize 14C dating and to introduce new dating methods for the Pleistocene.